A Century With Craniopagus Twin Separation Surgeries: Nihilism to Optimism. Issue 1 (6th July 2022) - Gupta, Deepak; Kedia, Shweta; Rath, Girija Prasad; Pandia, Mihir Prakash; Chauhan, Sandeep; Sharma, Rajeev; Raheja, Amol; Darbari, Shaurya; Kamra, Devasheesh; Malik, Vishwas; Saxena, Anita; Hote, Milind; et al.
Abstract : Craniopagus conjoined twins are extremely rare, reported 1 in 2.5 million live births. To date, 62 separation attempts in 69 well-documented cases of craniopagus twins have been made. Of these, 34 were performed in a single-stage approach, and 28 were attempted in a multistage approach. One or both twins died of massive intraoperative blood loss and cardiac arrest in 14 cases. We report our surgical experience with conjoined craniopagus twins (JB) with type III total vertical joining and shared circumferential/circular sinus with left-sided dominance. A brief review of the literature is also provided. In our twins, the meticulous preoperative study and planning by the multidisciplinary team consisting of 125-member, first-staged surgical separation consisted of creation of venous conduit to bypass part of shared circumferential sinus and partial hemispheric disconnection. Six weeks later, twin J manifested acute cardiac overload because of one-way fistula development from blocked venous bypass graft necessitating emergency final separation surgery. Unique perioperative issues were abnormal anatomy, hemodynamic sequelae from one-way fistula development after venous bypass graft thrombosis, cardiac arrest after massive venous air embolism requiring prolonged cardiopulmonary resuscitation, and return of spontaneous circulation at 15 minutes immediately after separation. This is the first Indian craniopagus separation surgery in a complex total vertical craniopagus twin reported by a single-center multidisciplinary team. Both twins could be sent home, but one remained severely handicapped. Adequate perioperative planning and multidisciplinary team approach are vital in craniopagus twin separation surgeries.